Medicaid healthcare expenditures for infants with birth defects potentially related to Zika virus infection in North Carolina, 2011–2016. Issue 2 (4th January 2022) - Bergman, Kristin; Forestieri, Nina E.; Di Bona, Vito L.; Grosse, Scott D.; Moore, Cynthia A.
Abstract: Background: In 2016, Zika virus (ZIKV) was recognized as a human teratogen. North Carolina (NC) had no local transmission of ZIKV but infants with relevant birth defects, including severe brain anomalies, microcephaly, and eye abnormalities, require specialized care and services, the costs of which have not yet been quantified. The objective of this study is to examine NC Medicaid healthcare expenditures for infants with defects potentially related to ZIKV compared to infants with no reported defects. Methods: Data sources for this retrospective cohort study include NC birth certificates, Birth Defects Monitoring Program data, and Medicaid enrollment and paid claims files. Infants with relevant defects were identified and expenditure ratios were calculated to compare distributions of estimated expenditures during the first year of life for infants with relevant defects and infants with no reported defects. Results: This analysis included 551 infants with relevant defects and 365, 318 infants with no reported defects born 2011–2016. Mean total expenditure per infant with defects was $69, 244 (median $30, 544) for the first year. The ratio of these expenditures relative to infants with no reported defects was 14.5. Expenditures for infants with select brain anomalies were greater than those for infants with select eye abnormalities only. Conclusions: Infants with defects potentially related to ZIKV had substantially higher Medicaid expenditures than infants with no reported defects. These results may be informative in the event of a future outbreak and are a resource for program planning related to care for infants in NC.